Examining The Reasons behind Third Molar Extraction; A Look Back in Time - Tooba Saeed; Nabeela Riaz; Samreen Younus; Saba Hanif; Hammad Latif; Rana Zeerak (Journal of Aziz Fatimah Medical and Dental College)
ABSTRACT Objectives: Extraction of third molar tooth is a frequently performed procedure in department of oral and Maxillofacial surgery, for various justified reasons. The objective of our study is to identify the reasons for extraction of third molar tooth in patients presenting at the University Dental Hospital, Lahore. Methodology: In May 2022, a retrospective study was carried out at The University of Lahore's University Dental Hospital. Records from the oral and maxillofacial surgery department were searched for relevant data between January 1, 2021, and December 31, 2021. There were 200 people in the sample. SPSS version 25 was used to compile and analyze the data. Standard descriptive analysis was initially performed, followed by chi-square analysis. Results: Records of 200 patients were gathered, with 56 percent being females and 44 percent males. Wisdom teeth extractions were more prevalent in patients aged between 31 to 40 years. Mandibular molar extractions were more common. Surgical methods were employed in 55 percent of cases, while non-surgical methods were used in 45 percent. Caries was the most prevalent reason for extraction, accounting for 64 percent, followed by mobility at 13 percent. Other reasons for extraction included broken root fragments and impaction, each contributing 9.5 percent. Pericoronitis was observed in 3.5 percent of cases, and orthodontic reasons were also noted. Conclusion: Individuals aged 18-40 predominantly underwent third molar extraction, with dental caries being the primary reason for extraction. Pericoronitis was major cause in the younger age group, whereas mobility was more common in the older age group. Prophylactic extraction was not widely practiced in our clinical setting.